Predictive approaches in drug discovery and development : biomarkers and in vitro/in vivo correlations - Williams, J. Andrew (Wiley series on technologies for the pharmaceutical industry., 2012)
Practical Utility of Biomarkers in Drug Discovery and Development covers all aspects of biomarker research applied to drug discovery and development and contains state-of-the-art appraisals on the practical utility of genomic, biochemical, and protein biomarkers. Case histories and lessons from successful and unsuccessful applications of biomarkers are included along with key chapters on GLP validation, safety biomarkers and proteomics biomarkers. Regulatory agency perspectives and initiatives both in the US and internationally are also discussed.